IMPLEMENTATION EXCISE REGULATIONS OF VAPE LIQUID IN KPPBC TIPE MADYA CUKAI MALANG - Sumantri, Joko (Politeknik Keuangan Negara STAN, 2019)
The study of e-cigarettes (vape) associated with excise is quite difficult to find in Indonesia. Thus, this study becomes important for the government in evaluating the application of vape liquid excise tax rules to make it fairer for businesses. By using a qualitative descriptive research method, this study obtained the findings that in the working area of KPPBC Type Madya Cukai Malang, the implementation of new regulations related to vape had increased the tobacco excise tax revenue by <1% of the total tobacco excise revenue in the Malang region. In Malang, the contribution of excise revenue from vape liquid is still relatively small to the overall excise tax revenue from tobacco products considering the quantity that is still not massive because it is a new product subject to excise. Although the socialization efforts related to this matter can be said to be successful, it is still needed a mechanism for channeling information for example through social networks so that the latest policies and regulations that are implemented can be implemented more effectively.